ChemInform Abstract: 1, 4‐Cyclohexadienes — Easy Access to a Versatile Building Block via Transition‐Metal‐Catalyzed Diels—Alder Reactions. Issue 37 (16th September 2014) - Hilt, Gerhard
Abstract Review: 51 refs.